PELATIHAN PIJAT LAKTASI BAGI KADER DI KELURAHAN TUAH KARYA WILAYAH KERJA PUSKESMAS SIDOMULYO KOTA PEKANBARU TAHUN 2021 - SEPTI INDAH PERMATA SARI,; JURAIDA ROITO HRP,; SISKA HELINA, (KRIDA CENDEKIA, 2021)
The presentation of exclusive breastfeeding in Indonesia in 2018 was 65.16%, this figure is still below the national target of 80%. Based on data from the Pekanbaru City Health Office in 2018, that exclusive breastfeeding coverage in Pekanbaru was 50.70% and the lowest exclusive breastfeeding coverage was in the working area of the Sidomulyo Health Center, which was 26.98. Based on a study conducted by Amalia (2019) at the Sidomulyo Health Center, Tampan District, of 789 infants aged 0-5 months recorded at the Sidomulyo Health Center, only 219 (27.75%) babies received exclusive breastfeeding. In the working area of the Sidomulyo Public Health Center itself, it consists of 3 sub-districts, of the 3 existing urban villages, the Tuah Karya sub-district has the lowest coverage, which is 33.9%. The purpose of this community service is to provide lactation massage training for cadres as an effort to increase the coverage of exclusive breastfeeding. Face-to-face activities were carried out 6 times. Each activity was carried out according to the schedule that had been prepared, namely, the first meeting was conducted to create a What's App Group and shared perceptions, at this meeting it was also agreed that the time would be used for training. At Meeting 2, pre-test and sharing activities were carried out with cadres and the Puskesmas. At the 3rd and 4th Meetings, the material was given on Lactation Management and Lactation Massage. At the 5th meeting, massage training was conducted. And for Meeting 6 the evaluation was carried out offline to assess the final ability of the cadres and a Post Test was carried out. The result of the activity is that the average knowledge of cadres has increased from 59.28 (SD 9.168) to 81.66 (SD 8.346). This means that there is an increase in the knowledge of cadres after being given training on lactation massage. Evaluation is carried out by cadres doing lactation massage to fellow cadres. From the evaluation carried out, it can be seen that the Cadre can do lactation massage in the Good category based on the results of the assessment using a checklist